Integration of Interactive Digital Media with Psycholinguistics and Ethnolinguistics to Enhance Students’ Arabic Reading Competence - Via Azka Lazuardina; Mochammad Imam Machfudi (Naatiq: Journal of Arabic Education, 2026)
The rapid development of digital technology has transformed language learning practices, yet Arabic reading instruction in many educational contexts still relies on conventional and text-centered approaches. This condition creates a gap between students’ cognitive needs and the learning environment, particularly in developing reading competence. Empirical data indicate that students’ Arabic reading proficiency remains at a low level, with national surveys showing that fewer than 40% of Indonesian secondary school students are able to comprehend Arabic texts beyond the literal level (refer to relevant national literacy data). Previous studies have highlighted the benefits of digital media in language learning; however, limited research integrates psycholinguistic and ethnolinguistic perspectives within interactive digital media for Arabic reading instruction. This gap is significant because psycholinguistic factors – such as cognitive processing, working memory, and inferential ability – alongside ethnolinguistic factors – such as cultural relevance and contextual meaning- making – are both essential dimension that determine reading comprehension quality. This study aims to examine the effectiveness of integrating interactive digital media grounded in psycholinguistic and ethnolinguistic principles to improve students’ Arabic reading competence. The study employed a quasi-experimental design with a pre-test and post-test control group structure conducted at a secondary-level educational institution (MTs). Data were collected through reading comprehension tests administered as pre-test and post-test. The results reveal that the experimental group achieved a significantly higher mean post-test score (M = 91.96) compared to the control group (M = 81.90), with a mean difference of 10.068 (p<.001), indicating a significant improvement in literal comprehension, inferential understanding, and vocabulary mastery. This study concludes that the integration of interactive digital media supported by cognitive and cultural approaches effectively enhances Arabic reading competence and offers a viable instructional model for Arabic language education in the digital era.